2011
DOI: 10.5761/atcs.cr.10.01652
|View full text |Cite
|
Sign up to set email alerts
|

Two Lung Adenocarcinomas in the Same Lobe: Multiple Primaries or Intrapulmonary Metastasis?

Abstract: Abnormal nodules were found in the left lung of a 52-year-old woman in segments 6 and 10 on a chest CT. These nodules showed no changes for 18 months, and we discontinued followup. Almost 5 years later, an abnormal shadow was found in her left lower lung field on a medical check-up chest X-ray. Chest CT revealed that the left segments 6 and 10 nodules had grown. We diagnosed these lesions as synchronous double primary lung cancers in the same lobe based on the disease history and performed a left lower lobecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…According to Ono’s study, the sum value of the differences in the expression ratio of four proteins (p53, p16, p27, and c-erbB2) was evaluated in immunohistochemically stained specimens among multiple primary lung cancers and intrapulmonary metastasis [ 29 ]. Yoshimoto reported a case, diagnosed as double primaries, that is distinguished by EGFR gene mutation analysis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Ono’s study, the sum value of the differences in the expression ratio of four proteins (p53, p16, p27, and c-erbB2) was evaluated in immunohistochemically stained specimens among multiple primary lung cancers and intrapulmonary metastasis [ 29 ]. Yoshimoto reported a case, diagnosed as double primaries, that is distinguished by EGFR gene mutation analysis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma in situ of the lung was frequently associated with EGFR gene mutation [15,16]. There is a case of multiple adenocarcinomas in situ of the lung having the same mutation of EGFR in common [17]. …”
Section: Resultsmentioning
confidence: 99%
“…According to Martini's criteria, this case would be diagnosed as primary adenocarcinoma and its pulmonary metastasis. However, Junji et al reported a case of synchronous lung cancers that shared the same EGFR mutation [4]. Takuwa et al [5] reported a similar case of double primary cancers with identical histological findings.…”
Section: Discussionmentioning
confidence: 99%